An experimental study on vortex-induced vibration response of marine riser with and without semi-submersible. (May 2018) - Domala, Vamshikrishna; Sharma, Rajiv
This article presents an experimental study on 'vortex-induced vibrations' of marine riser that is mounted on a semi-submersible. The marine riser is considered as a flexible cylindrical member made of Stainless Steel Braided Flexible Hose that is fixed at both the ends. Our experimental conditions are carefully chosen to represent real world applications, and Stainless Steel Braided Flexible Hose riser acts as both the drilling and catenary riser. We report the experimental studies conducted in the current flume for three cases: Stainless Steel Braided Flexible Hose as drilling riser by tensioning, Stainless Steel Braided Flexible Hose as catenary riser, and Stainless Steel Braided Flexible Hose as catenary riser with semi-submersible. Our aspect ratio (length to diameter) of Stainless Steel Braided Flexible Hose drilling riser is 86 and Stainless Steel Braided Flexible Hose catenary riser is 157 (effective ratio till touchdown point), and Reynolds's number is up to 5000. The experimental conditions are as follows: for Case 1 – tension of 43 N with empty pipe, with water, with drilling mud conditions and effective length decreased with water and increasing the tension up to 67 N with water; for Case 2 – catenary Stainless Steel Braided Flexible Hose with empty pipe condition and with water; for Case 3 – Stainless Steel Braided Flexible Hose catenary riser with semi-submersible at0 ∘, 30 ∘, 45 ∘, 60 ∘, and90 ∘ current directions. The accelerometer signals are filtered and integrated to get the displacements, and the isolation of low frequencies obtained from semi-submersible is implemented to get the pure displacement of Stainless Steel Braided Flexible Hose. We report the results for transverse vibration and our results show that the maximum response for Stainless Steel Braided Flexible Hose drilling riser occurs at around reduced velocity of 6 and for Cases 2 and 3 at around reduced velocity of 9. Also, the Stainless Steel Braided Flexible Hose drilling riser with water shows higher response as compared to other cases (with and without drilling fluid), and increasing the tension results into increase of the natural frequency and decreased response when compared to other cases (with and without drilling fluid). Furthermore, for the same amplitude of vibration, Stainless Steel Braided Flexible Hose drilling riser with drilling fluid shows higher equivalent lift coefficients. The Stainless Steel Braided Flexible Hose catenary riser without fluid shows a minimum transverse response compared with fluid, and Stainless Steel Braided Flexible Hose's response with semi-submersible is minimum compared with individual Stainless Steel Braided Flexible Hose riser with water. Finally, we show that the reported results offer meaningful deep insights into the vortex-induced vibration response of marine riser for real world applications.